NURSING CARE FOR PEOPLE WITH VENOUS ULCER: CASE REPORT - Santos Lima, Maria Karoline (2023)
Objective: To report nursing care to patients with venous ulcers and the impact on the user's quality of life. Methodology: This is a qualitative study of the case report type with a qualitative design, following the checklist of the Case Report Guidelines (CARE) of the EQUATOR Network. Results: In the present study, it was possible to observe the healing evolution of a venous ulcer located in the right lower limb, the periodic evaluations under photographic record and therapeutic adherence adopted in each procedural step for better understanding and integral evaluation of the user. Conclusions: Thus, upon completing the treatment and follow-up with the user, it was noticed that he presented a significant improvement in his quality of life, improving his social and family life, in addition to a better perception of his self-esteem and self-image. Keywords: Case reports; Venous ulcer; wound healing; Nursing Assistance